Manual de procesos para la empresa pública ESPAM MFL-EP - Caicedo García, Karen Andrea (2023)
The present investigative work had as objective the elaboration of a process manual for the standardization of the activities that are carried out in each one of the areas at EP-ESPAM "MFL". For this investigation three phases were defined, as a first phase the respective visit was carried out where the interview was applied to the Manager of the company, which allowed establishing a direct contact in the institution and identifying the processes that are carried out, later proceeded to carry out the collection of information to the seven workers of the institution through the process files, it is so, that using the American National Satandar Institute ANSI symbology the flow charts were elaborated, allowing to have a visual analysis that reflected the sequence in the activities, where due to the great amount of processes managed by the company, a prioritization matrix was made to graph the most relevant, then the process manual was developed as a tool for the timely organization of processes and contribution to workers to guide them in an orderly manner in the execution of activities. The results determined the existence of 46 threads, of which 12 were prioritized according to their impact with the company, with the client and with the objective, in addition to their importance in the process. The realization of the manual of processes for the company allowed the standardization of the procedures and activities that are carried out in the different departmental areas, constituting a written and illustrative guide for the personnel of the institution.